TITIK BALIK SEKSUALITAS DI KALANGAN KAUM MUDA - Efendi, Zakaria; Abdullah, Irwan (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
This article explores the shifting meaning of sexuality among urban adolescents, particularly females, highlighting a trend towards the desacralization of intimate relationships. This issue is critical as it reflects the broader transformation of social values and cultural norms influenced by globalization, social media, and gender awareness. In addition, this study also responds to the lack of studies that address lifestyle and prostitution in a more reflective and anthropological manner. Using a qualitative approach, this research was conducted in Yogyakarta involving five female university students and who are also prostitutes. Data was collected by conducting observations and conducting in-depth interviews. The main findings show that social media and pop culture play an important role in accelerating the desacralization of sexuality, while traumatic experiences contribute to risky sexual behavior. This study concludes that the desacralization of sexuality among adolescents is influenced by bad sexual experiences, and that social media and pop culture encourage more permissive sexual expressions, shifting meanings of sexuality among adolescents have shaped more flexible perceptions of sexuality. The study recommends developing sexual education policies that are inclusive and responsive to changing social norms, as well as raising awareness of the long-term impact of sexual trauma on adolescents.